2022
DOI: 10.1002/hipo.23452
|View full text |Cite
|
Sign up to set email alerts
|

Intact high‐resolution working memory binding in a patient with developmental amnesia and selective hippocampal damage

Abstract: Debate continues regarding the possible role of the hippocampus across short-term and working memory tasks. The current study examined the possibility of a hippocampal contribution to precise, high-resolution cognition and conjunctive memory.We administered visual working memory tasks featuring a continuous response component to a well-established developmental amnesic patient with relatively selective bilateral hippocampal damage (Jon) and healthy controls. The patient was able to produce highly accurate resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In measures of color-location memory, Jon’s recognition accuracy matched the highest achieving control participant, while his reconstruction performance was superior to 6 of the 7 controls (Allen et al, 2014). Across four tasks measuring binding between color and orientation or color and location using simultaneous or sequential presentation of stimuli, Jon’s response accuracy was high, and always numerically superior to the control mean (Allen et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In measures of color-location memory, Jon’s recognition accuracy matched the highest achieving control participant, while his reconstruction performance was superior to 6 of the 7 controls (Allen et al, 2014). Across four tasks measuring binding between color and orientation or color and location using simultaneous or sequential presentation of stimuli, Jon’s response accuracy was high, and always numerically superior to the control mean (Allen et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…While patient KA displayed few, if any, residual episodic abilities, this patient was able to accurately retrieve semantic memories, and show evidence of superior or even very superior access to these memories than controls. Another patient with DA, patient ‘Jon’, has often produced response accuracy levels that are at least higher than those of control participants in previous experimental explorations of visuospatial working memory (Allen et al, 2022, 2014; Baddeley et al, 2010). Jon was at least numerically superior to the control mean on recognition-based measures of shape-color binding (Baddeley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the SN–VTA has long been attributed as source of the memory-enhancing dopaminergic inputs [35,38,43], recent findings point to a denser innervation by the LC that can provide noradrenergic as well as dopaminergic signals [41,45,46]. Here we compared the association of the two catecholaminergic centers with an extensive set of tasks that are thought to depend more (episodic memory) or less (working memory) on hippocampal processing [108,115]. We observed that LC integrity was specifically related to late-life episodic memory performance (as compared to working memory or fluid intelligence) and that this association was stronger than the SN–VTA–episodic memory relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies always used a limited set of colours or shapes, leading open the suggestion that Jon's problem might be with the precision of responding (Ekstrom & Yonelinas, 2020;Yonelinas, 2013). Although this proved not to be the case in this instance (Allen et al, 2022), there is evidently potential value to be gained from looking at major phenomena using both methodologies. This has been nicely illustrated by studies of visual working memory for color showing that performance reflects a combination of categorical and continuous information (Bae et al, 2015;Hardman et al, 2017), with the precise nature of the representation appearing to vary depending on the task that is implemented (Ricker et al, 2022).…”
mentioning
confidence: 93%